PENGGUNAAN MEDIA PUISI DIGITAL BERBASIS VISUAL AUDIO KINESTETIK UNTUK MENINGKATKAN KEMAMPUAN MENULIS PUISI RUMPANG BERDASARKAN GAMBAR - Prabowo, Eko Budi; Gusrayani, Diah; Iswara, Prana Dwija (Jurnal Pena Ilmiah, 2017)
Due to the problem of the research based on students who still lacking on writing skill esspecially unoccupied poem based on picture. Early data was November 8th 2016 that from 21 students, only 1 students who reached the target or only 4,76%. The purpose of this research to improved learning process and also learning result at 3rd grade Sukakerta Elementary School. The altenatif to solved problem by applying Digital Poem Visual Basis Kinestetic Audio Media. Class action research which has four steps applied were plan, action, observation, and reflection. Due to the result research proved that media affected to improved student result learning about writing poem learning. Writing poem skill also included word structure, verse, line at unoccupied poem. The increased result inclued three cycles were teacher performance about plan at 1st cycles reached 80%, 2nd cycles reached 91% and 3rd cycles reached 100%. Teacher performance about process learning at 1st cycles reached 78%, 2nd cycles reached 90% and 3rd cycles reached 100%.Â  Student activity at 1st reached 23% with good criteria, 2nd cycles got 47% with excellent criteria, 3dr cycles reached 100% with excellent criteria. Result learning at 1st cycles reached 47,61%, 2nd cycles got 71,42%, and 3rd cycles reached 85,71%. The conlusion of this research that by applying Digital Poem Visual Basis Kinestetic Audio Media improved writing skill of unoccupied poem based on picture.Â Â